Study of vitamin B12 status and the consequential clinico-hematological profile in healthy vegetarian population in Nepal - Paudel, Pramod; Agrawal, Jagdish Prasad; Timilsena, Santosh; Subedi, Jyoti (Journal of Chitwan Medical College, 2017)
Background: A strict vegetarian diet has been associated with an increased risk of vitamin B12 deficiency. Clinical manifestations of cobalamin deficiency are hematologic and neurological symptoms. The purpose of this study was to determine the prevalence of vitamin B12 deficiency in healthy vegetarian population and to study the clinical and hematological profile of vitamin B12 deficient subjects.Methods: A community based cross-sectional observational study was conducted through preplanned camps in Kathmandu Nepal. 166 vegetarian people were investigated for serum vitamin B12 level and their hematological profile was done. They were examined for neurological manifestation of vitamin B12 deficiency.Results: The mean serum vitamin B12 level of the vegetarian in this study was 271.34 ±241.74 pg/ml (mean ± SD)., 53.6 % had serum vitamin B12 deficiency. 56.5 % of male and 47.1 % of female had vitamin B12 deficiency. The risk of vitamin B12 deficiency is more in males than females with odds ratio 1.201 (CI=95%) which is not statistically significant with p-value 0.312. There was no significant difference in vitamin B12 level in different age group.The study population had mean hemoglobin of 13.12 ± 1.72 gm/dl. Anemia was present in 34.9 % of study population. 33.9 % of male and 37.3 % of female had anemia. There was no significant difference in anemia in male and female vegetarian (p-value 0.72). 40% of patient who had vitamin B12 deficiency had anemia.A significant low hemoglobin level and higher MCV were found as level of serum vitamin B12 decreased. Only one patient had macrocytic anemia.There were few symptoms but not specific to vitamin B12 deficiency.Conclusion: The result of present study show that prevalence of vitamin B12 deficiency among healthy vegetarian was 53.6% with higher prevalence in male and elder age group.Prevalence of anemia was 34.9% in this study with elderly group and females being more affected.There was significant correlation between vitamin B12 and hemoglobin level and significant negative correlation with MCV. Although, not significant, leucocytes count, lymphocyte count and platelets were low in vitamin B12 deficient population.Few clinical features were present in vitamin B12 deficient subjects but neurological features specific to vitamin B12 deficiency were not seen.